The Influence of Digital Marketing and Sales Promotion on Purchase Decisions: The Mediating Role of Brand Awareness - Venny Handryani; Hery Winoto Tj (Goodwood Publishing, 2026)
Purpose: To analyze the influence of digital marketing through social media on promoting fast instant spices and how sales promotion strategies affect consumer purchase decisions, mediated by brand image, specifically for Sasa House Japanese Curry products. Methodology: This study employed a quantitative approach with purposive sampling. Questionnaires were distributed to 100 respondents who visited supermarkets in DKI Jakarta. Data analysis used Structural Equation Modeling (SEM) with SmartPLS. Results: Digital Marketing (X1) significantly influences brand awareness (Z), with a t-value of 5.696 and a p-value of 0.000, confirming the hypothesis. Sales Promotion (X2) significantly impacts Purchase Decisions (Y), though the influence is weaker, with a t-value of 1.994 and a p-value of 0.046. Both Digital Marketing and Sales Promotion affect Consumer Purchase Decisions through Brand Awareness for Sasa House Japanese Curry. Conclusions: Digital marketing strategies, particularly through social media, and sales promotions play important roles in shaping consumer purchase decisions for Sasa House Japanese Curry. Brand awareness mediates these processes, suggesting that strengthening the brand image could boost sales. Limitations: The study is limited by the sample size of 100 respondents from DKI Jakarta, which may not represent the broader population. The influence of sales promotions was modest, indicating the need for further research on additional factors affecting purchase decisions. Contributions: This research enhances understanding of how digital marketing and sales promotions influence consumer behavior, highlighting brand awareness as a mediator and offering valuable insights for marketers.